Pengaruh Citra Merek, Kualitas Produk, dan Online Customer Reviews Terhadap Keputusan Pembelian Pada Produk Skincare The Originote di Kota Surakarta - Fera Valentina; Nina Adelina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Examining how Surakarta consumers make the study aims to understand purchasing decisions. Online user reviews, product quality, and brand perception all affect Originote skincare goods. As more individuals become aware of how essential It seeks to maintain the welfare of their skin, the demand for skincare products is increasing. The Originote, a Chinese a skincare brand launched in Indonesia market in 2022, faces intense competition in the wake of the beauty industry's explosive growth. The Originote has issues with overclaiming some of its products, which could affect consumers' purchasing decisions even when the company sells moderately priced goods with eye-catching designs. Participants in this survey-based study are internet shoppers from Surakarta who purchase The Originote products. The study's conclusions demonstrate that product quality and online customer evaluations have a considerable and positive influence on purchasing decisions, whereas brand image has a significant and unfavorable impact. This implies that consumers regard product quality and user reviews more than brand impression when making purchases. It is recommended that The Originote enhance the caliber of its products and its response to online reviews in order to boost consumer confidence and competition in the Indonesian skincare sector.